Os Elementos Terras Raras nas Apatitas do Maciço Alcalino de Anitapolis, SC - PEREIRA, VITOR; FORMOSO, MILTON; DUTRA, CLAUDIO; FIGUEIREDO, ANA (Pesquisas em Geociências, 1996)
The rare Earth elements from apatites of alcaline igneous rocks and carbonatites of Anitápolis were analysed by ICP and neutronic activation. The apatites, from magmatic, hydrothermal and weathering facies, were separated by different techniques. The results display the characteristic pattern from apatites of alkaline rocks in which the light rare earth elements are enriched in comparison with the heavy ones. The hydrothermal apatites are richer in total contents of REE, and also their La / Yb and LREE / HREE ratios are higher. Calculations or enrichment of different LREE led to conclude that results by ICP and neutronic activation are similar and that the apatites from Anitápolis are poorer in La, Ce, Yb and Lu in comparison with different patterns.